Phase Space Generation for Proton and Carbon Ion Beams for External Users’ Applications at the Heidelberg Ion Therapy Center - Tessonnier, Thomas; Marcelos, Tiago; Mairani, Andrea; Brons, Stephan; Parodi, Katia (Frontiers in Oncology, 2016)
In the field of radiation therapy, accurate and robust dose calculation is required. For this purpose, precise modeling of the irradiation system and reliable computational platforms are needed. At the Heidelberg Ion Therapy Center (HIT), the beamline has been already modeled in the FLUKA Monte Carlo code. However, this model was kept confidential for disclosure reasons and was not available for any external team. The main goal of this study was to create efficiently phase space (PS) files for proton and carbon ion beams, for all energies and foci available at HIT. PS are representing the characteristics of each particle recorded (charge, mass, energy, coordinates, direction cosines, generation) at a certain position along the beam path. In order to achieve this goal, keeping a reasonable data size but maintaining the requested accuracy for the calculation, we developed a new approach of beam PS generation with the Monte-Carlo code FLUKA. The generated PS were obtained using an infinitely narrow beam and recording the desired quantities after the last element of the beamline, with a discrimination of primaries or secondaries. In this way, a unique PS can be used for each energy to accommodate the different foci by combining the narrow-beam scenario with a random sampling of its theoretical Gaussian beam in vacuum. PS can also reproduce the different patterns from the delivery system, when properly combined with the beam scanning information. MC simulations using PS have been compared to simulations including the full beamline geometry and have been found in very good agreement for several cases (depth dose distributions, lateral dose profiles), with relative dose differences below 0.5%. This approach has also been compared with measured data of ion beams with different energies and foci, resulting in a very satisfactory agreement. Hence, the proposed approach was able to fulfill the different requirements and has demonstrated its capability for application to clinical treatment fields. It also offers a powerful tool to perform investigations on the contribution of primary and secondary particles produced in the beamline. These PS are already made available to external teams upon request, to support interpretation of their measurements.